Pengaruh Pupuk Organik Cair Daun Kelor Dengan Penambahan Ekstrak Limbah Kulit Buah Kakao Terhadap Pertumbuhan Tanaman Bayam - STYANING TYAS, ELIN TIARA HAYU, Dra. Aminah Asngad, M.Si (2016)
Cocoa crop waste and Moringa leaves are usually just thrown away and can disturb the environment if not handled properly. Cocoa shell waste has a content of nitrogen, calcium and magnesium. So it can be used as raw material for the manufacture of liquid organic fertilizer to trigger plant growth. This study used an experimental method with two factors, one is the concentration of fertilizer (P1 = 40%, P2 = 50%, and P3 = 60%) and factor 2 interval watering liquid fertilizer (I1 = 3 days, I2 = 4 days and I3 = 5 days) with 9 treatments and two replications. The parameters observed were plant height, number of leaves, and the wet weight. Observations were made every two weeks for one month. Data were analyzed with ANOVA treatment two lanes. The results showed that the combination of the best treatments for high growth stems ie on P3I1, while the combination of the best treatment for the growing number of leaves and wet weight is on P1I3. There is an interaction effect between the concentration of fertilizer watering intervals on the growth of stem height and the number leaves. But, on a wet weight growth was no interaction effect between these two factors.